PREVALENCE OF HP INFECTION AMONG ADULTS ATTENDING MEDICAL SERVICES AT OUR LADY OF CONSOLANTA KISUBI HOSPITAL. A CROSS SECTIONAL STUDY. - Ssekitoleko , Anthony; Nakiyingi , Jane (Student's Journal of Health Research Africa, 2024)
Objectives; The study’s specific objectives were to determine the prevalence of Hp infection among adult female and male patients who attended medical services at Our Lady of Consolanta Kisubi Hospital from March to April 2018 and to as well establish the relationship between gender and Hp infection among adults. Methodology; It was a cross-sectional study and data was collected from 100 samples collected from clients aged 18 years and above. The samples were selected using consecutive Sampling techniques and analyzed using H.pylori qualitative antibody rapid test kits. The data and results of the analysis were then collected from the laboratory request forms and reported on the checklist. This was then analyzed using simple Excel data sheet analysis and graphically presented in the form of tables and pie charts Findings; The study showed that the prevalence of prevalence of Hp infection among female patients that attended Our Lady of Consolanta Kisubi Hospital was found to be 21.6% and that for male adults was found to be 30.6%. The study has further established that there is no clear relationship between gender and Hp infection since prevalence in males was seen to be 9% higher than that in females which can be easily related to poor feeding time management among men. Conclusion; The study showed that the prevalence of Hp infections among adult patients tat attended Our Lady of Consolanta Kisubi Hospital was found to be 26.0%. Recommendations; I therefore recommend that Our Lady of Consolanta Kisubi Hospital works with the Ministry of Health to scale up sensitization of the public and healthcare workers about Hp infection and the risks associated with the infection. Also, I recommend that a broader study be carried out on Hp infection to have a broader picture concerning the infection and its management.